Implementation of Community Service from a Women's Perspective in Strengthening Leadership and Governance at Pondok Pesantren Al-Islami Kebon Jambu Cirebon - Angellyta, Putry Sally; Muthmainnah, Yulianti (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2025)
The development of Pondok Pesantren Al-Islami Kebon Jambu Cirebon, as a traditional Islamic educational institution, represents a strategic urgency in ensuring its relevance and effectiveness amid the dynamics of the digital era. Special emphasis is placed on the gender perspective, considering that the pesantren is led by a female religious leader (Ibu Nyai), whose leadership reflects a strong and influential female presence. This study aims to critically examine the impact of multidisciplinary community service on strengthening pesantren governance, especially in supporting women’s leadership and building a gender-responsive pesantren system. A qualitative case study approach was adopted using a feminist framework. Data collection involved participatory observation, in-depth interviews, literature review, and collaborative practices through the KKN PLUS (Community Service or Kuliah Kerja Nyata) PLUS. The activities engaged male and female students from diverse academic backgrounds, including Architecture, Visual Communication Design, Informatics Engineering, Information Systems, Accounting, and Management. The results show that the initiative contributed not only to technical aspects such as the design of physical facilities and digitalization of financial management but also strengthened the managerial capacity of the pesantren, particularly in supporting women-led leadership. Furthermore, multidisciplinary integration generated holistic and coordinated solutions, especially in the application of information systems, enhancement of financial literacy, and the design of infrastructure that accommodates the needs and comfort of female students. Therefore, this community service initiative functions as a medium of social transformation that not only improves institutional quality but also affirms the strategic role of women within the pesantren environment.